Illuminating species diversity of nudibranch in Indonesian coral reef ecosystem using molecular identification. Issue 1 (December 2021) - Dharmawan, I G W D; Bengen, D G; Setyobudiandi, I; Subhan, B; Verawati, I; Sani, L M I; Madduppa, H
Abstract: Nudibranch has high species diversity with complex morphological characters and is challenging to identify at the species level. The lack of knowledge about nudibranchs makes it difficult to identify conventionally using morphological characters. This study aims to identify nudibranchs at the species level using the DNA barcoding method from the mitochondrial cytochrome oxidase 1 (CO1) gen. The results of DNA barcoding using the Cytochrome Oxidase I (COI) gene showed 18 species of 51 samples analyzed. The phylogenetic tree reconstruction revealed 11 main clades belonging to 11 genera. The genetic distance between and within species clearly shows the difference between individuals. Interspecific genetic distance shows the lowest value between species was found between Chromodoris annae and Chromodoris magnifica is 0.075, and the largest genetic distance observed between species Glossodoris rufomarginata and Tritonidae sp is 0.354. This study shows molecular analysis can be used to identify nudibranch up to species level, which will be a source of information in knowing the distribution and the genetic distance.